Archery training improve postural control in young children - Lee, A.; Chiu, Y. C.; Liu, Y. F.; Lin, W. H. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Exercise training might be beneficial for postural control (PC) during exercise and daily activities. The purpose of the study was to examine the effects of an eight-week archery training program on PC in young children during the standard, aiming, and archery shooting standing posture.